2020
DOI: 10.3390/ijerph17082646
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Negative Life Events on Suicidal Ideation in College Students: The Role of Rumination

Abstract: This study aimed to investigate the influence of negative life events on suicidal ideation in college students and the role of rumination. Using a cluster sampling method, 894 college students were asked to fill out the adolescent life event scale, ruminative response scale, and suicidal ideation scale. The study revealed the following: (1) negative life events, rumination, and suicidal ideation were significantly positively correlated with each other; (2) rumination played a full mediating role in the influen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 38 publications
4
15
0
Order By: Relevance
“…One important purpose of this study is to provide evidence for the relationship between negative focused disposition and suicidal ideation. Our study showed that negative focused disposition was positively associated with suicidal ideation among Chinese college students, which was consistent with previous studies ( 9 , 12 ). Hypothesis 1 was supported.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…One important purpose of this study is to provide evidence for the relationship between negative focused disposition and suicidal ideation. Our study showed that negative focused disposition was positively associated with suicidal ideation among Chinese college students, which was consistent with previous studies ( 9 , 12 ). Hypothesis 1 was supported.…”
Section: Discussionsupporting
confidence: 93%
“…It is also a negative view of the world, including a negative view of oneself and the future ( 9 , 10 ). Scholars have concluded that people who completed suicide may struggle with negative thoughts until the last moment of their lives ( 11 ), which indicates that pessimistic predictions of future events are associated with the risk of suicidal ideation ( 12 ). College students are probably under more pressure today than they have been in more than 20 years ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…Our findings suggest that it is essential to examine RT's association with suicidal ideation among individuals with GD, as it is conducive to poor mental health outcomes. Wang et al reported similar results when analyzing RT as a mediating component of negative life events and suicidal ideation, in a sample of cisgender university students ( 43 ).…”
Section: Discussionmentioning
confidence: 61%
“…In addition, among common theories in the explanation between negative mental and suicide risk, rumination plays an essential role. Wang reported a significant association of negative mental with suicidal ideation among college students beyond the effects of rumination 44 . It is possible that migrant workers with negative mental were more vulnerable to the negative effects of perceived stress, and this kind of reflective rumination process eventually increased their suicide risk.…”
Section: Discussionmentioning
confidence: 98%